STRES DAN DAMPAKNYA TERHADAP PRESTASI KERJA PEGAWAI NEGERI SIPIL - Lubis, Kartika Sari (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
This study aims to determine the impact of stress on the performance of civil servants (PNS). Subjects in this study are civil servants Education and Culture amounted to 58 people. The research method used is descriptive and quantitative method. Data analysis using validity test, reliability test and normality test with the help of SPSS 16, using simple linear regression analysis, obtained calculation of regression equation that is: Y '= 42,519 - 0,068X. Coefficient of negative value means there is a negative relationship between work stress with work performance, which means if the work stress increases, then the performance of work will decrease